FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN AKTIVITAS KOLINESTERASE DARAH PADA PETANI JAMBU DI DESA PESAREN KECAMATAN SUKOREJO KABUPATEN KENDAL - Irwan Hermawan; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Pesticide poisoning is a very dangerous condition that can cause acute or chronic poisoning, causing various kinds of health disorders, diseases and can also cause death from poisoning pesticides. Pesticide poisoning can be detected by looking at cholinesterase levels in the blood. Meanwhile, based on preliminary studies that have been done, guava plants are plants that need dilukan intensive care, and also on cashew farmers in the Village Pesaren known that there are already symptoms caused by poisoning pesticides such as dizziness, nausea and headaches. This study aims to analyze factors related to blood cholinesterase activity in guava farmers in Pesaren Village, Sukorejo District, Kendal District. The research design used was Analytical Descriptive with Cross Sectional approach. The population in this study were all members of farmer group of Pesaren Village which amounted to 50 people. Sampling technique using Purpossive Sampling with number of sample counted 48 people. The research instrument used was Cholinesterase Kit I Edson Method and Questionnaire. Measurement of cholinesterase in blood is by using Cholinesterase Kit I Edson Method. Statistical analysis using Chi-Square test. The results showed that there was a relationship between Age, Education, Work Period, Exposure Time, spraying direction, spraying position, knowledge, attitude, and management of pesticide have substantial relation with cholinesterase activity in guava peasant's blood. While the sex, frequency of pesticide use, the amount of pesticides mixed in one spraying of pesticides and the dose of pesticide mixing there is no substantial relationship with the activity of cholinesterase in the guava peasant's blood. The authors suggest that farmers seek information on the dangers of pesticides and how to use good and proper pesticides to the government and local health centers to pay attention to the health of the village community, especially the farmers who use pesticides by promotive and preventive efforts and regular health checks on activities cholinesterase to residents to prevent the negative effects of pesticide poisoning.